2016
DOI: 10.1080/07357907.2016.1235709
|View full text |Cite
|
Sign up to set email alerts
|

4-Chlorbenzoyl Berbamine, a Novel Derivative of the Natural Product Berbamine, Potently Inhibits the Growth of Human Myeloma Cells by Modulating the NF-κB and JNK Signalling Pathways

Abstract: Multiple myeloma (MM) remains incurable despite the development and the use of new agents. In our studies, we found that 4-chlorbenzoyl berbamine (BBMD9), a novel synthetic derivative of berbamine, inhibited the proliferation of MM cells in dose- and time-dependent manners. Flow cytometric (FCM) analysis revealed that MM cells were arrested in the G1 phase and that apoptotic cells increased in a time-dependent manner. Moreover, the BBMD9 treatment downregulated IKKα and IKKβ, inhibited p-IκBα, and blocked p65 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“… 13 , 16 Some studies report that BBM exerts its anticancer effect through inducing apoptosis, which is mediated by the regulation of various pathways, such as JNK/AP-1, Calmodulin-dependent protein kinase II and smad3 pathways. 13 , 17 , 18 Moreover, a literature search in the database indicates that there are some studies focusing on the chemosensitization effect of BBM. BBM and its derivatives could enhance the antitumor effect of paclitaxel, docetaxel and gemcitabine.…”
Section: Discussionmentioning
confidence: 99%
“… 13 , 16 Some studies report that BBM exerts its anticancer effect through inducing apoptosis, which is mediated by the regulation of various pathways, such as JNK/AP-1, Calmodulin-dependent protein kinase II and smad3 pathways. 13 , 17 , 18 Moreover, a literature search in the database indicates that there are some studies focusing on the chemosensitization effect of BBM. BBM and its derivatives could enhance the antitumor effect of paclitaxel, docetaxel and gemcitabine.…”
Section: Discussionmentioning
confidence: 99%
“…Xu et al ( 36 ) showed that the berbamine derivatives affect the Ca 2+ -stimulated Mg 2+ -dependent ATPase in erythrocyte membranes. Liang et al ( 37 ) reported that 4-chlorbenzoyl berbamine as a novel derivative of berbamine, could inhibit the growth of human myeloma cells by modulating the NF-κB and JNK signaling pathway. Meanwhile, a few previously published studies ( 15 , 24 , 25 ) also reported the berbamine induced SMMC-7721 cell apoptosis in the other signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that the antitumor effects of BBM in a variety of tumors, including breast cancer [19], myeloma [7,20], hepatoma [9,21], prostatic neoplasms [9], pancreatic carcinoma [22] and lung cancer [23]. Jin [22] con rmed that BBM signi cantly downregulated the expression of the antiapoptotic proteins such as Bcl-2 and Bcl-xL and inhibited proliferation in pancreatic carcinoma cells.…”
Section: Discussionmentioning
confidence: 97%